Biochemical characterization of cardiolipin synthase mutations associated with daptomycin resistance in enterococci (2013)
Daptomycin (DAP) resistance in enterococci has been linked to mutations in genes that alter the cell envelope stress response (CESR) (liaFSR) and changes in enzymes that directly affect phospholipid homeostasis, and these changes may alter membrane composition, such as that of cardiolipin synthase (Cls). While Cls substitutions are observed in response to DAP therapy, the effect of these mutations on Cls activity remains obscure. We have expressed, purified, and characterized Cls enzymes from both Enterococcus faecium S447 (residues 52 to 482; Cls447a) and Enterococcus faecalis S613 (residues 53 to 483; Cls613a) as well as Cls variants harboring a single-amino-acid change derived from DAP-resistant isolates of E. faecium. E. faecium Cls447a and E. faecalis Cls613a are tightly associated with the membrane and copurify with their substrate, phosphatidylglycerol (PG), and product, cardiolipin (CL). The amount of PG that copurifies with Cls is in molar excess to protein, suggesting that the enzyme localizes to PG-rich membrane regions. Both Cls447aH215R and Cls447aR218Q showed an increase in Vmax (μM CL/min/μM protein) from 0.16 ± 0.01 to 0.26 ± 0.02 and 0.26 ± 0.04, respectively, indicating that mutations associated with adaptation to DAP increase Cls activity. Modeling of Cls447a to Streptomyces sp. phospholipase D indicates that the adaptive mutations Cls447aH215R and Cls447aR218Q are proximal to the phospholipase domain 1 (PLD1) active site and near the putative nucleophile H217. As mutations to Cls are part of a larger genomic adaptation process, increased Cls activity is likely to be highly epistatic with other changes to facilitate DAP resistance.